2013 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--22605
|View full text |Cite
|
Sign up to set email alerts
|

The Inverted Classroom in a First-Year Engineering Course

Abstract: The Ohio State University. She has been on the staff of Ohio State's University Center for the Advancement of Teaching, in addition to teaching in both the physics department and college of engineering. Her research interests address a broad spectrum of educational topics, but her specialty is in how people learn problem solving skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 6 publications
0
10
0
2
Order By: Relevance
“…Although there is much discussion about flipping the class, there is little consistency in the definition of the term, causing confusion about what is being examined (Margulieux et al 2014). Many definitions of flipped learning focus on the use of video lectures outside of class, with class time devoted to in-class activities that help students apply and practice what was learned outside of class (Bergmann and Sams 2012; Carpenter and Pease 2012; EduCause 2012; Hamdan et al 2013; Morin et al 2013; Tucker 2012). However, critics point out the problems with this definition: flipped classes relying on lectures delivered via videos are simply replicating a pedagogical model proven to have many limits (Bligh 2000).…”
Section: The Flipped Classmentioning
confidence: 99%
“…Although there is much discussion about flipping the class, there is little consistency in the definition of the term, causing confusion about what is being examined (Margulieux et al 2014). Many definitions of flipped learning focus on the use of video lectures outside of class, with class time devoted to in-class activities that help students apply and practice what was learned outside of class (Bergmann and Sams 2012; Carpenter and Pease 2012; EduCause 2012; Hamdan et al 2013; Morin et al 2013; Tucker 2012). However, critics point out the problems with this definition: flipped classes relying on lectures delivered via videos are simply replicating a pedagogical model proven to have many limits (Bligh 2000).…”
Section: The Flipped Classmentioning
confidence: 99%
“…Bu öğrenme modelinde, sınıf içinde öğretmenlerin bilgi aktarımı rolünü bırakarak, öğrenciye devamlı geri bildirimler sağlayan rehber rolünü üstlenmesi (King, 1993;Milman, 2012) ve öğrencinin merkezde olduğu aktif öğrenme ortamlarının oluşturulması amaçlanır (Baker, 2000). Temel düzeydeki bilgiler öğretmenler tarafından paylaşılan kaynak ve materyaller ile ders öncesine (Milman, 2012), ev ödevi, tartışma ve uygulama gibi daha zor aktiviteler ise sınıf içine alınarak sınıf içi ve sınıf dışı faaliyetler yer değiştirilir (Morin et al, 2013).…”
Section: Ters Yüz Edilmiş Sınıflarunclassified
“…The inverted classes were well received by the instructors and the students, however, some students indicated that the inverted class required more time than traditional version, perhaps due to the post-lecture problem-solving sessions. Morin, et al 10 implemented an inverted classroom in the delivery of a first-year engineering course. The study involved several instructors and several sections of the class, which had previously been taught entirely in a traditional lecture mode.…”
Section: Background On Blended Coursesmentioning
confidence: 99%